Determinant of e-accounting (EA) adoption among Malaysian maritime SMES - Mohamad Ghaffar, Affizah; Zulkifli Mokhtar, Mohd; Nur Syahida Wan Ismail, Wan; Rosni Othman, Mohamad (International Journal of Engineering and Technology, 2018)
Good financial management will ensure improved performance of a company, especially a small company and so the company can compete and survive in their respective industries. Maritime industry as a high-tech industry has a significant contribution to our economy can be regarded as an imperative scope. Small Medium Enterprise (SME) mostly collapse due to poor financial management. The using of information technology (IT) in Accounting Information System (AIS) acts as crucial medium in creating a high-quality of financial management expecting better performance. This study attempts to identify determinants concerning the e-accounting (EA) adoption, particularly in the maritime industry for Malaysian SMEs. It intended at finding out the factors that led to e-accounting adoption by applying TOE (Technology, Organization and Environment) theory. A survey design was adopted in the form of a structured questionnaire with 7 Likert scale of point, which was used to collect data from 103 of owner-managers from SMEs maritime industry in Malaysia. Analysis took the form of computation of means and regression utilizing SPSS 21.0 software. Four independent variables namely technological, organizational, environmental and decision-maker have been examined for the predictor of the EA adoption. Organizational variable was attained to have a significant influence on IT adoption in AIS for maritime small business (Î² = 0.38). The overall results showed that 44.4% of the variables can explain key factors in determining the deployment of EA among Malaysian maritime SMEs. Future research should take into consideration of SMEs from other maritime nations worldwide.Â